Chimpanzee fathers bias their behaviour towards their offspring. Issue 11 (November 2016) - Murray, Carson M.; Stanton, Margaret A.; Lonsdorf, Elizabeth V.; Wroblewski, Emily E.; Pusey, Anne E.
Abstract : Promiscuous mating was traditionally thought to curtail paternal investment owing to the potential costs of providing care to unrelated infants. However, mounting evidence suggests that males in some promiscuous species can recognize offspring. In primates, evidence for paternal care exists in promiscuous Cercopithecines, but less is known about these patterns in other taxa. Here, we examine two hypotheses for paternal associations with lactating mothers in eastern chimpanzees ( Pan troglodytes schweinfurthii ): paternal effort, whereby males associate and interact more with their own infants, and mating effort, whereby males invest in mothers and offspring for mating privileges. We found that fathers associated more with their offspring than they did with non-kin infants, particularly early in life when infanticide risk is highest. Additionally, fathers and their infant offspring interacted more than expected. Notably, association between fathers and mother–infant pairs did not predict the probability of siring the mother's next offspring. Our results support the paternal effort, but not the mating effort hypothesis in this species. Chimpanzees are one of the most salient models for the last common ancestor between Pan and Homo, thus our results suggest that a capacity for paternal care, possibly independent of long-term mother–father bonds, existed early in hominin evolution.